INEQUALITIES IN PROSTATE CANCER ONCOLOGY CARE IN THE BRAZILIAN AMAZON: DIAGNOSTIC, THERAPEUTIC, AND PROGNOSTIC IMPACTS - Fiore, Carlos Eduardo da Vitória; Abrahim, Maria Eduarda; Rodrigues, Juliana Barreto; Oliveira, Maria Eduarda Silva; Barreto, Ádria de Araújo; Lelis, Marjore de Oliveira; Facci, Ricardo (Seven Editora, 2026)
This chapter critically analyzes inequalities in the diagnosis and treatment of prostate cancer in the Northern region of Brazil, with emphasis on geographic barriers, structural limitations of the oncology care network, treatment delays, and social determinants that directly affect clinical outcomes. Evidence from national databases and multicenter studies demonstrates a higher frequency of late-stage diagnosis, substantially longer travel distances to access radiotherapy, and reduced availability of therapies with proven survival benefit in the Amazon region. In addition, racial, socioeconomic, and territorial vulnerabilities among Indigenous, riverine, and quilombola populations further aggravate disparities in access to early diagnosis and timely treatment. The Amazonian scenario highlights the urgent need for public health policies guided by equity, expansion of oncology infrastructure, telehealth strategies, and culturally adapted interventions to improve prostate cancer outcomes in underserved populations.